2017
DOI: 10.5901/mjss.2017.v8n1p285
|View full text |Cite
|
Sign up to set email alerts
|

Issues in Malaria Communication in Enugu, Southeast Nigeria

Abstract: Communication plays an important part in health promotion. Malaria affects millions of people worldwide, and is a major

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, this kind of activity is good, it only needed to be expanded to clean the Anopheles mosquitoes breeding places like in along river, water springs, hoard puddles, hoard unused fish ponds, and to reduce twigs / midribs so that the sunlight could penetrate through those places . Research in Enugu Southeast Nigeria concluded that there is a need for audience-specific communication and attitudinal change to ensure the uptake improvement [19]. Malaria control socialization in Kulonprogo and Magelang were delivered as one of malaria vector control efforts.…”
Section: Resultsmentioning
confidence: 99%
“…However, this kind of activity is good, it only needed to be expanded to clean the Anopheles mosquitoes breeding places like in along river, water springs, hoard puddles, hoard unused fish ponds, and to reduce twigs / midribs so that the sunlight could penetrate through those places . Research in Enugu Southeast Nigeria concluded that there is a need for audience-specific communication and attitudinal change to ensure the uptake improvement [19]. Malaria control socialization in Kulonprogo and Magelang were delivered as one of malaria vector control efforts.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that exposure to behaviour change communication (BCC) is a positive predictor of LLIN use ( 3 , 4 , 5 ), and effective in raising public awareness and knowledge of malaria ( 6 , 7 , 8 , 9 , 10 ). This is important because misconceptions about the cause of malaria often result in rejection of promoted malaria control measures ( 9 , 11 , 12 ) However, there are other variables such as place of residence that affect use of nets.…”
Section: Introductionmentioning
confidence: 99%
“…It is pertinent to note that these traditional arts and craft industries are always an important aspect of culture. They constitute viable cultural attractions Okpoko and Okpoko (2002) noted that cultural attractions are indispensable components of tourism development schemes. They provide a foundation upon which tourist trade should be built.…”
Section: Introductionmentioning
confidence: 99%